Global analysis of an expectations augmented evolutionary dynamics - ANTOCI, Angelo (Institutional Knowledge at Singapore Management University, 2008)
We consider a deterministic evolutionary model where players form expectations about future play. Players are not fully rational and have expectations that change over time in response to current payoffs and feedback from the past. We provide a complete characterization of the qualitative dynamics so induced for a two strategy population game, and relate our findings to standard evolutionary dynamics and equilibrium selection when agents have rational forward looking expectations.